2022
DOI: 10.3390/foods11233870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turmeric and Aloe Vera Extract on Shelf-Life of Goat and Buffalo Admixture Milk Paneer during Refrigeration Storage

Abstract: The present study was undertaken to evaluate efficacy of turmeric and aloe vera extract in extending shelf life of goat milk paneer. The paneer was made by admixing goat milk and buffalo milk in the ratio of 60:40 so as to achieve a standard fat 4.5%. The treatment group, T1, was made by adding 5 mL/100 mL (v/v) of turmeric extract in heated milk before coagulation. Similarly, 5 mL/100 mL (v/v) aloe vera extract was added to heated milk for group T2 while T3 was prepared by adding both turmeric extract 5 mL/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Studies reported that licorice has a number of compounds, primarily glycyrrhizin, triterpene, saponins and phenolics, which have antioxidant and immune-regulatory potential (Aslam et al, 2020). Similar increase in TBARS values was also observed by Umaraw et al (2022) in goat and buffalo milk paneer.…”
Section: Lipid Oxidationmentioning
confidence: 64%
See 3 more Smart Citations
“…Studies reported that licorice has a number of compounds, primarily glycyrrhizin, triterpene, saponins and phenolics, which have antioxidant and immune-regulatory potential (Aslam et al, 2020). Similar increase in TBARS values was also observed by Umaraw et al (2022) in goat and buffalo milk paneer.…”
Section: Lipid Oxidationmentioning
confidence: 64%
“…The decrease in the sensory attributes of curd balls might be due to the oxidative and microbial deterioration of the lipid and protein molecules. Similarly, labneh incorporated with licorice extract was rated well by sensory panelists (Al-Turki et al, 2008), and in goat-buffalo admixture milk paneer added with turmeric and aloe vera (Umaraw et al, 2022).…”
Section: Sensory Evaluationmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, [23] reported significantly lower aerobic plate counts in frankfurters added with 1-1.2% shiitake mushroom powder, while [24] observed significant antimicrobial effect of shiitake stipe extract in fermented sausages against E coli. Phtyocompounds such as phenolic acids, flavonoids, guggulsterones, [25,26]. Significantly higher values in SPC and psychrophile count was observed from day 9 in the control than treatments, while a significant difference in coliform and yeast and mould count was observed on the last day.…”
Section: Change In Microbialmentioning
confidence: 91%